Tedhakan serat babad Banyumas: suntingan teks, terjemahan, dan fungsi genealogi dalam kerangka struktur naratif = Manuscript on Banyumas History: Text edition, translation, and the genealogical function in the contect .. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Tedhakan Serat Babad Banyumas (next abbreviated into TSBB) is the only Babad Banyumas manuscript containing Sejarah Pangiwa (no TSBB containing Sejarah Panengen), namely the genealogical tree from Adam Prophet up to Kings of the Majapahit. And then, Kings of Majapahit are related to the genealogical three of the Banyumas Dynasty founder. The aim of this research is to describe the physique of TSBB and other Babad Banyumas manuscripts and to review their intertextual attributions. TSBB selected as individual text is not yet published. Accordiningly, TSBB is necessary to be edited and translated in their texts. Furthermore, interaction of two elements in TSBB text, those are genealogy and narrative entities enable to place the function of hand the meaning of the mentioned texts. This study is by making us of filolo cal approach, namely the Babad Banyumas texts are compared. And then TSBB selected as individual text. Because of the TSBB is the only text containing Sejarah Pangiwa, so the editing method of its text is a single manuscript method in edition standard. Apart from the filoloOcal approach, it is also car- ried out the literary opproach, especially the structural analysis, that is the interaction of two TSBB's textual elements. Here, an interview is carried out to give the description of their text and traditions. The comparison of 32 texts indicates that there are six versions of Babad Banyumas, namely Mertadiredjan Manuscript (verse), tranformation manuscripts of Merta-diredjan Manuscript (prose), Traditional of Dipayudan Ma-nuscript (verse), a lot of Wirjaatmadjan Manuscript (prose), that of Danuredjan (verse), and that of Danuredjan (prose). TSBB belongs of the first version. Infractions of two TSBB's textual elements attempts to emphasize the ideal image of Manguni Bagus Mangun as Banyumas Dynasty founder. MangunThe ideal image of Mangun built by a legitimacy system involving the patront-client relation, genealogical relation to Majapahit-Pajajaran, application of Javanese classification pattern mancapat, application of a title nunggak semi, prohibitions, predictions, creese prize, supranatural voice (wangsit), pulrung (divine reve-lation), selection of sacred regions, and mangun's role as an ancestor of Banyumas Dynasty Most strikingly, Mangun is realted to the genealogcal tree of Adam Prophet up to Kings of Majapahit (Sejarah Pangiwa).